Transient transfection of the enteric parasite Entamoeba histolytica and expression of firefly luciferase. - Purdy, J E (1994)
Development of DNA-mediated transfection in Entamoeba histolytica will facilitate basic research toward the control of this protozoan parasite. A transient transfection system was established by using the firefly luciferase gene ligated to the 5' and 3' flanking regions of the amebic hgl1 gene. The optimal construct tested encoded an hgl1-luciferase fusion protein and contained 1 kb of 5' flanking sequence with 16 bases of coding sequence from the hgl1 gene ligated in-frame to the luciferase start codon and 2.3 kb of 3' flanking sequence from hgl1 ligated 3' to the luciferase stop codon. Optimal electroporation conditions in strain HM-1:IMSS trophozoites when using this construct were 500 microF and 500 V/cm, which resulted in luciferase activity up to 5000-fold above background 9-12 hr after electroporation. Constructs that contained the luciferase gene without amebic flanking sequences or that contained a simian virus 40 promoter, enhancer, and polyadenylylation signal produced only background levels of luciferase activity. The ability to introduce and express genes in amebae will now permit a genetic analysis of the virulence of this organism, which remains a serious threat to world health.